2018
DOI: 10.3390/brainsci8120222
|View full text |Cite
|
Sign up to set email alerts
|

The Genetic Diagnosis of Neurodegenerative Diseases and Therapeutic Perspectives

Abstract: Genetics has led to a new focus regarding approaches to the most prevalent diseases today. Ascertaining the molecular secrets of neurodegenerative diseases will lead to developing drugs that will change natural history, thereby affecting the quality of life and mortality of patients. The sequencing of candidate genes in patients suffering neurodegenerative pathologies is faster, more accurate, and has a lower cost, thereby enabling algorithms to be proposed regarding the risk of neurodegeneration onset in heal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 155 publications
0
21
0
Order By: Relevance
“…Several common features of neurodegeneration have been studied and associated to the molecular pathogenesis of AD, PD, and ALS, and these include neuroinflammation, autophagy, and oxidative stress [ 7 , 8 ]. Moreover, pathogenic mutations, amyloid precursor proteins, superoxide dismutase, and DNA and RNA binding proteins are important contributing factors to these neurodegenerative diseases [ 9 ]. Although many common features have been found and studied, other emergent mechanisms remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Several common features of neurodegeneration have been studied and associated to the molecular pathogenesis of AD, PD, and ALS, and these include neuroinflammation, autophagy, and oxidative stress [ 7 , 8 ]. Moreover, pathogenic mutations, amyloid precursor proteins, superoxide dismutase, and DNA and RNA binding proteins are important contributing factors to these neurodegenerative diseases [ 9 ]. Although many common features have been found and studied, other emergent mechanisms remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…The importance of genetics in the development of neurodegenerative diseases has been studied extensively in the last two or more decades [ 43 - 47 ]. These studies have demonstrated the central role played by genes in the aetiopathogenesis of these disorders.…”
Section: Introductionmentioning
confidence: 99%
“…The exact factors and aetiology of neurodegenerative diseases are still unknown but various risk factors such as environmental pollutants, familial history and genetic variants at several gene loci have been identified [ 16 ]. The hereditary cause of neurodegenerative diseases is well-established and there are recent advances exploring the possible use of genetic sequencing of various genetic markers in the diagnosis of neurodegenerative diseases [ 17 ].…”
Section: Neurological Disordersmentioning
confidence: 99%